Peran Ibu Dalam Pembelajaran Daring Di Era Covid 19 Di Kelurahan Jongaya Kota Makassar - Andi Anggun Dwiutari; Darman Manda; Andi Octamaya Tenri Awaru (Universitas Negeri Makassar, 2022)
This study aims to 1) examine and describe the form of the mother's role in helping children in online learning during the covid 19 pandemic, 2) the impact of mothers accompanying children in online learning. This type of research uses descriptive qualitative research by determining the number of informants consisting of 10 informants selected by purposive sampling technique with the criteria of housewives having a career and having children attending elementary schools (SD) in Jongaya Village. Data collection techniques used are observation, interviews, and documentation. The data validation technique used is source triangulation. The results showed that 1) the form of the mother's role in helping children in online learning during the Covid-19 pandemic in Jongaya Village, namely the first role of the mother as a teacher at home or as a facilitator, the second role of the mother as a motivator, and the third role of the mother as a supervisor/director, 2) positive impact, namely mothers can know directly the development of children's education. Meanwhile, the negative impact is that there is less time for rest due to increased workload, less time to play with family because free time is used to do office work (career), mothers become more emotional because children do not focus on tasks and play a lot.